MESO-CENOZOIC ACCUMULATION HISTORY OF THE AFRICANMARGIN OF THE EQUATORIAL ATLANTIC - (:unkn) unknown (My University, 2017)
The objective of the Transform Source to Sink Project (TS2P) is to link the dynamics of the erosion ofthe West African Craton to the offshore sedimentary basins of the African margin of the Equatorial Atlanticat geological time scales. This margin, alternating transform and oblique segments from Guinea to Nigeria,shows a strong structural variability in the margin width, continental geology and relief, drainage networksand subsidence/accumulation patterns. We analyzed this system combining onshore geology andgeomorphology as well as offshore sub-surface data.We defined offshore basins stratigraphic architectures of the 3 sub-basins (Sierra Leone /Liberia, IvoryCoast and Ghana / Togo / Benin) and used these to establish their terrigeneous accumulation histories includingthe whole depositional system (from the shoreline to the most distal deposits onto the oceanic crust). We thencorrected these from remaining porosity after compaction as well as in-situ production (mainly carbonates)established from well-data. We included uncertainties related to the time to depth conversion, biostratigraphy,porosity and in-situ production corrections. We discuss our results in terms of Saddler effect for the most recenttime periods. Accumulations in the three basins show increased rates during the Cenomanian, Maastrichtianand Oligocene.We compare these accumulation histories to paleogeographic maps established at the scale of WestAfrica spanning the continental domain and offshore basins since 200 Ma and discuss their source to sinkimplications during the opening of Equatorial Atlantic. The Cenomanian accumulation may be related to theerosion of the remaining rift-shoulder following continental break-up. The Maastrichian increase inaccumulation could be related to either the tectonic inversion of western Africa at the time or to climatic changeaffecting erosion capacity in the continental drainage area. The Oligocene peak is contemporaneous of a majordrainage reorganiza
Keywords: African Research